SOME MODERN METHODS OF TEACHING FOREIGN LANGUAGES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In recent decades, the field of foreign language teaching has undergone significant transformation due to globalization, technological advancement, and changing educational needs. Traditional grammar-centered approaches are increasingly being replaced by learner-centered and communicative methods that emphasize practical language use. This article examines some of the most effective modern methods of teaching foreign languages, including the Communicative Language Teaching approach, Task-Based Learning, Content and Language Integrated Learning (CLIL), Blended Learning, and the use of digital technologies. The analysis highlights the advantages of these methods in developing communicative competence, learner autonomy, and motivation. The article concludes that the integration of modern methodologies enhances the effectiveness of foreign language instruction and better prepares learners for real-life communication.